2020
DOI: 10.3390/jcm9072314
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Biofeedback Training on Esophageal Peristalsis in Amyotrophic Lateral Sclerosis Patients with Dysphagia

Abstract: Esophageal manometry (EM) could serve as an objective method for the detection of esophageal peristalsis in patients with amyotrophic lateral sclerosis (ALS). In this group of patients, biofeedback training (BT) using the EM procedure is a promising method for the rehabilitation of swallowing function. A total of 20 ALS patients with clinical evidence of dysphagia and who met WFN criteria were recruited for this study. The standard transnasal EM with solid-state transducers was performed, and swallows with wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“… 22 , 92 ) In addition, a recent study in patients with amyotrophic lateral sclerosis and ED showed that biofeedback is a promising method. 93 ) However, our experts made a weak recommendation in the presence of OPD because of the requirement for special training and equipment and serious patient cognitive skills. Among other modalities, it can be used in the presence of suitable conditions and patients.…”
Section: Discussionmentioning
confidence: 99%
“… 22 , 92 ) In addition, a recent study in patients with amyotrophic lateral sclerosis and ED showed that biofeedback is a promising method. 93 ) However, our experts made a weak recommendation in the presence of OPD because of the requirement for special training and equipment and serious patient cognitive skills. Among other modalities, it can be used in the presence of suitable conditions and patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the BP group, there were 13 patients: 8 women and 5 men; the mean age of patients at disease onset was 63.0 ± 6.7 years. Mean values in the ALSSSS were: 6.7 ± 1.9 (7-5 range), mean duration of dysphagia was correspondingly: 7.9 ± 3.7 months (range: [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Mean disease duration from the occurrence of first symptoms to the date of inclusion in the study was 7-70 months (mean: 16.4 ± 12.3).…”
Section: Subjectsmentioning
confidence: 99%
“…It is well documented that dysphagia in amyotrophic lateral sclerosis (ALS) is presented with changes in the oral and pharyngeal phase of swallowing [3][4][5][6]. The occurrence of the changes in the esophageal phase of swallowing is rarely described in the literature, and there are controversial data regarding its pathology and the involvement of UES in the impaired swallowing mechanism in ALS patients.…”
Section: Introductionmentioning
confidence: 99%
“…O biofeedback EMG na disfagia neurogênica tem sido usado em casos de acidente vascular cerebral (AVC) (16) , doença de Alzheimer (17) , e esclerose lateral amiotrófica (18) , apresentando melhora da função de deglutição e redução da incidência de resultados adversos. Uma revisão sistemática recente sobre casos de DP incluiu apenas dois estudos abordando o uso de biofeedback EMG para tratar disfagia nessa população (19) .…”
Section: Introductionunclassified